Implementasi Pedidikan Karakter Religius melalui Pembiasaan di SMA IT Mahmudiyyah Kecamatan Cicurug Kabupaten Sukabumi - Fauziahmp, Siti Salma; Makhfudz, Makhfudz; Nurmiati, Ai Siti (Universitas Pakuan, 2025)
THE IMPLEMENTATION OF RELIGIOUS CHARACTER EDUCATION THROUGH HABITUATION AT MAHMUDIYYAH IT HIGH SCHOOL, CICURUG DISTRICT, SUKABUMI REGENCY The problem in this study stems from the importance of religious character education amidst the challenges of globalization and the negative influence of an increasingly complex social environment. The purpose of this study is to describe and analyze the implementation of religious character education through the habituation method in one of the Islamic-based high schools in Sukabumi Regency. This study used a qualitative approach with descriptive methods, and data were obtained through observation, in-depth interviews, and documentation. The results showed that habituation activities were carried out in a planned manner through various daily, weekly, and incidental religious activities aimed at instilling religious values, discipline, responsibility, and social awareness. The role of teachers as role models, parental involvement, and a supportive school environment were the main supporting factors. Meanwhile, obstacles faced included a lack of student understanding, the influence of social media, and limited competence of educators. The conclusion of this study is that the habituation method is an effective strategy in instilling religious character when implemented consistently and involving synergy between schools, families, and the community. The implications of this study indicate the need for ongoing collaboration to strengthen religious value-based character education in the school environment.